KODE ETIK PUSTAKAWAN DALAM MELAYANI PEMUSTAKA DI PERPUSTAKAAN SEKRETARIAT DAERAH PROVINSI KALIMANTAN - Bunyau, Agustinus; Priyadi, Antonius Totok (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractLibrary of the Regional Province Kaliamantan the West is the library in the government agency that usually provide the books, in accordance with the institution where the library. In a library in managed by the librarian that all activities in the library can run smoothly, but to be a librarian, that was a professional should have good etiquette and in accordance with the organized on the code of ethics the librarian. In applying the code of ethics you will be influential on the quality of service in the library, the quality of the library as well as the quality of the librarian itself. The purpose of this research is to find out how understand a librarian of the code of conduct for librarians and relatedness of the librarians serving visitors over. In returns the data to complete the job The end, the author to use the method of deskriptip to approach a qualitative one where the author directly dealing with librarians as well as straight to conduct observations, interviews, and documentation in straight to the library. It would be done with the librarian, head of administration and office, head of personnel and the library, as well as four people visirots over. In the Library of the Secretariat of the Regional Province Kaliamantan the West could not be said to be in accordance with standard code of conduct by the librarian of indonesia because librarian who do not understand and do not apply as a whole of the code of conduct for librarians who have been set. Therefore, the librarian will try and learn about the application of the code of ethics the librarian for the sake of improving the image of the library and the quality of the librarian in order to fit in with SNP.Â The key : the Code The librarian, the Library, SNP, Service.Â